2020
DOI: 10.1002/cpp.2511
|View full text |Cite
|
Sign up to set email alerts
|

The effect of desire thinking on facilitating beliefs in alcohol use disorder: An experimental investigation

Abstract: Permissive beliefs relate to the acceptability of engaging in alcohol use in spite of obvious potential negative consequences. They are considered the most proximal and precipitating cognitive factor in the decision to use alcohol and/or the activation of strategies to obtain it. Recent research suggested that ‘desire thinking’ may be involved in the escalation of craving and addictive behaviours and can play a role in strengthening permissive beliefs. The current study tested whether the induction of desire t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…Impulsivity may lead to addictive behaviour without any self‐controlling, thinking and premeditation bypassing higher‐order thinking (Ostafin et al, 2008) which would include desire thinking. On similar lines, a study has found that metacognitions, known as the activating beliefs in desire thinking (Caselli & Spada, 2015), had no mediating role in the relationship between impulsivity and problematic smartphone use (Casale et al, 2021). In addition, it is possible that impulsivity may be more closely associated with behavioural constructs rather than cognitive processes (e.g., desire thinking) so that a study also has shown that desire thinking is more correlated with behavioural aspects of impulsivity (i.e., motor impulsivity) than its cognitive facets (i.e., intentional impulsivity and non‐planning) (Aydın et al, 2022).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Impulsivity may lead to addictive behaviour without any self‐controlling, thinking and premeditation bypassing higher‐order thinking (Ostafin et al, 2008) which would include desire thinking. On similar lines, a study has found that metacognitions, known as the activating beliefs in desire thinking (Caselli & Spada, 2015), had no mediating role in the relationship between impulsivity and problematic smartphone use (Casale et al, 2021). In addition, it is possible that impulsivity may be more closely associated with behavioural constructs rather than cognitive processes (e.g., desire thinking) so that a study also has shown that desire thinking is more correlated with behavioural aspects of impulsivity (i.e., motor impulsivity) than its cognitive facets (i.e., intentional impulsivity and non‐planning) (Aydın et al, 2022).…”
Section: Discussionmentioning
confidence: 93%
“…In individuals with AUD, desire thinking has been found to strengthen permissive beliefs about alcohol use (Caselli et al, 2021) and increase craving and alcohol‐related behaviours (Caselli et al, 2016, 2017; Kavanagh et al, 2009; Martino et al, 2017, 2019; Solem et al, 2020). Individuals with nicotine dependence experience high levels of desire thinking beyond negative affect and nicotine craving (Caselli, Nikcevic, et al, 2012; Solem et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…As with other affective and cognitive processes specific for addictive disorders (e.g., craving, cue reactivity), desire thinking is observable among substance-use disorders as well as addictive behaviors and internet-use disorders, respectively. It has been investigated in the context of problem alcohol drinking [8,[14][15][16][17][18][19] next to a few studies on tobacco use [5,20,21] and eating behaviors [22][23][24] and successively gains an attentional focus among addictive behaviors (for a meta-analysis, see [25•]) and specific internet-use disorders. As such, it has been investigated in the context of gaming [26][27][28][29], pornography viewing [27,30], social networks use [20,27], shopping and gambling [27], and the general use of the internet [5, 7, 31•, 32, 33], indicative of its relevance among (potentially problematic) online behaviors.…”
Section: Introductionmentioning
confidence: 99%
“…Vacillation is the scourge of the writer and the barrier to success and this quality is found in every endeavor of human existence. In part, it stems from permission giving thoughts , a behavior that is well recognized and understood in drug and alcohol addiction: “I’ll do it tomorrow, next week, never..” . Recognizing this phenomenon is important as it is a behavior that can be corrected.…”
Section: Vacillationmentioning
confidence: 99%